Development of Wind Turbines used on Iraqi Exterior Highways - Abd, Ikram Kamel; Mhel, Shahad Raji; Abed, Aseel Kamel; Yaseen, Waleed Ibrahim; Al-Juboori, Omar (Iraqi Journal of Science, 2025)
The design and production of four-blade vertical turbines for wind power are the subjects of this study. One kind of wind turbine with a vertical axis that is used to generate electricity is the giromill wind turbine. The turbine comprises a primary shaft that rotates and four straight airfoils that depict the blades. The airfoil, main shaft, and bearing of all necessary wind turbine components were developed for the Iraqi exterior highways in this study. Included in the power calculations are torque, TSR, power factor, and wind speed. After the blades are made, all the pieces are assembled from steel, aluminum, and wood components. Ultimately, testing revealed that the turbine was operating very efficiently.